Analisis Kesalahan Berbahasa dalam Artikel Jurnal Semantik Vol. 3 No. 4: Studi Kasus pada Artikel Analisis Teks Eksposisi Ruangguru - Petra Putri Sarinah Pandiangan; Arief Rachman Pakpahan; Gracia Lovian Girsang; Herdita Ginting; Zara Marsanda Mahisa; Yolani Erawati (Simpati, 2026)
This study aims to identify and explain language errors in a scientific journal article entitled "Analysis of Language Errors in Expository Texts on the Digital Platform 'Ruangguru', August 2024 Edition as a Reading Resource for High School Students," published in the Semantik Journal, Issue 3, Number 4. The method applied in this study is descriptive qualitative using a literature study approach. For data collection, observation and recording techniques were used, while data analysis was carried out using the content analysis method. The findings of this study revealed 27 language errors divided into five categories, including 12 spelling errors (typos) (44.4%), 5 word choice errors (18.5%), 4 punctuation errors (14.8%), as well as ineffective sentence structure errors and errors in the bibliography (3 each) (11.1%). The causes of these errors include minimal editing process, inadequate understanding of PUEBI (Indonesian Standards for Ethics and Education), and inaccuracies from the author. This study shows that articles analyzing language errors still contain errors, so there is a need for improvements in the quality of editing by the author and the journal's editorial team.